First articulated skeleton of Palaeeudyptes gunnari from the late Eocene of Isla Marambio (Seymour Island), Antarctica - Acosta Hospitaleche, Carolina Ileana Alicia (2010)
The first articulated skeleton of a penguin from the late Eocene of Antarctica is described. MLP 96-I-6-13 comes from the upper Submeseta Allomember (La Meseta Formation) of Isla Marambio (locality DPV 10/84). The significance of this finding in the context of the Anthropornis nordenskjoeldi biozone is discussed. An osteologic description of the recovered elements and a brief discussion of its systematic determination are provided. MLP 96-I-6-13 is the first articulated skeleton with sure specific assignment to Palaeeudyptes gunnari (Wiman, 1905), a species previously known only through isolated tarsometatarsi and included in the groups of Wiman.